A novel computed tomography radiomic nomogram for early evaluation of small airway dysfunction development - Cui, Sijia; Shu, Zhenyu; Ma, Yanqing; Lin, Yi; Wang, Haochu; Cao, Hanbo; Liu, Jing; Gong, Xiangyang (Frontiers in Medicine, 2022)
The common respiratory abnormality, small airway dysfunction (fSAD), is easily neglected. Its prognostic factors, prevalence, and risk factors are unclear. This study aimed to explore the early detection of fSAD using radiomic analysis of computed tomography (CT) images to predict fSAD progress. The patients were divided into fSAD and non-fSAD groups and divided randomly into a training group (n =190) and a validation group (n =82) at a 7:3 ratio. Lung kit software was used for automatic delineation of regions of interest on chest CT images. The most valuable imaging features were selected and a radiomic score was established for risk assessment. Multivariate logistic regression analysis showed that age, radiomic score, smoking, and history of asthma were significant predictors of fSAD (P < 0.05). Results suggested that the radiomic nomogram model provides clinicians with useful data and could represent a reliable reference to form fSAD clinical treatment strategies.